Explanations for Unsuccessful Weight Loss Among Bariatric Surgery Candidates - Hwang, Kevin O. (2008)
BACKGROUND: Our objective was to analyze subjective explanations for unsuccessful weight loss among bariatric surgery candidates. METHODS: This was a retrospective analysis of 909 bariatric surgery candidates (78.2% female, average body mass index [BMI] 47.3) at a university center from 2001 to April 2007 who answered an open-ended question about why they were unable to lose weight. We generated a coding scheme for answers to the question and established inter-rater reliability of the coding process. Associations with demographic parameters and initial BMI were tested. RESULTS: The most common categories of answers were nonspecific explanations related to diet (25.3%), physical activity (21.0%), or motivation (19.7%), followed by diet-related motivation (12.7%) and medical conditions or medications affecting physical activity (12.7%). Categories related to time, financial cost, social support, physical environment, and knowledge occurred in less than 4% each. Men were more likely than women to cite a medical condition or medication affecting physical activity (19.2% vs 10.8%, P=0.002, odds ratio [OR]=1.96, 95% confidence interval [CI]=1.28–2.99) but less likely to cite diet-related motivation (7.1% vs 14.2%, P=0.008, OR=0.46, 95% CI=0.26–0.82). CONCLUSIONS: Our findings suggest that addressing diet, physical activity, and motivation in a comprehensive approach would meet the stated needs of obese patients. Raising patient awareness of under-recognized barriers to weight loss, such as the physical environment and lack of social support, should also be considered. Lastly, anticipating gender-specific attributions may facilitate tailoring of interventions.